Intracranial tumors of the central nervous system and air pollution - a nationwide case-control study from Denmark - Aslak Harbo Poulsen; Ulla Arthur Hvidtfeldt; Mette Sørensen; Robin Puett; Matthias Ketzel; Jørgen Brandt; Camilla Geels; Jesper H. Christensen; Ole Raaschou-Nielsen (BMC, 2020)
Abstract Background Inconclusive evidence has suggested a possible link between air pollution and central nervous system (CNS) tumors. We investigated a range of air pollutants in relation to types of CNS tumors. Methods We identified all (n = 21,057) intracranial tumors in brain, meninges and cranial nerves diagnosed in Denmark between 1989 and 2014 and matched controls on age, sex and year of birth. We established personal 10-year mean residential outdoor exposure to particulate matter < 2.5 μm (PM2.5), nitrous oxides (NOX), primary emitted black carbon (BC) and ozone. We used conditional logistic regression to calculate odds ratios (OR) linearly (per interquartile range (IQR)) and categorically. We accounted for personal income, employment, marital status, use of medication as well as socio-demographic conditions at area level. Results Malignant tumors of the intracranial CNS was associated with BC (OR: 1.034, 95%CI: 1.005-1.065 per IQR. For NOx the OR per IQR was 1.026 (95%CI: 0.998-1.056). For malignant non-glioma tumors of the brain we found associations with PM2.5 (OR: 1.267, 95%CI: 1.053-1.524 per IQR), BC (OR: 1.049, 95%CI: 0.996-1.106) and NOx (OR: 1.051, 95% CI: 0.996-1.110). Conclusion Our results suggest that air pollution is associated with malignant intracranial CNS tumors and malignant non-glioma of the brain. However, additional studies are needed.